Improvement of Document Security Against Aes-192 Algorithm Based Trojan Attacks (Advanced Encryption Standard): Peningkatan Keamanan Dokumen Terhadap Serangan Trojan Berbasis Algoritma Aes-192 (Advanced Encryption Standard) - Irmayana Sunarti (Sakura Publisher, 2023)
Document security is the protection of information contained in documents from threats and risks that may arise, both from physical attacks and cyber attacks, one of which is a trojan attack. An algorithm is a solution or method of document security that is appropriate for maintaining the confidentiality and authenticity of documents, and can improve the security aspects of a document or information. The algorithm used in enhancing document security to encrypt and decrypt documents is the AES-192bit algorithm (Advanced Encryption Standard). The method used is the waterfall method which consists of literature studies, system analysis, system design, implementation and testing. The resulting application is an AES encryption and decryption application using the web-based AES-192 algorithm method. This application is intended to secure documents in the following formats: .docx, .xls, .xlsx, .pdf and .text. The results of the study can be concluded that increasing data security using the AES-192 algorithm is successful. The encryption process is carried out to produce data that is not easy to read and not easily hacked by others unless they have the key to decrypt the data. The key used to encrypt and decrypt is the same. If the key used is the same then the data can be used, but if it is different then the result will not be read.